Comprehensive small-signal stability analysis for master hybrid MMC connected with strong and weak AC systems. (November 2021) - Lu, Xiaojun; Li, Mengbo; Lei, Xiao; Yang, Zhangbin; Peng, Daixiao; Luo, Daijun
Abstract: The small-signal stability problem of power electronic converters has always been a critical concern for safe operation. This paper conducts a comprehensive analysis of the small-signal stability for the hybrid modular multilevel converter (MMC), which is promising in the application of future over-head-line high-voltage-direct-current transmission. The impacts of the strong and weak AC system connection are comparatively researched through eigenvalue-based analysis. The newly emerging factors that hamper the stability are identified for the weak AC system integration. The work in this paper provides valuable guidance for robust control parameter configuration of the hybrid MMC.